Analysis of state procurement in Colombia against corruption, a case study of the public tender contract ECP-SOC-001—2006, of the modernization project of the Refinería de Cartagena S.A (Reficar) (2020)
In this essay it is analyzed the general statute of state contracting and the modifications over the years. It emphasized was placed on the public bidding, one of the state’s contracting modalities, actually the most important. Which consists on the selection of the applicant that offers the highest value for a good or a service. However, there have been presented irregularities in this type of contract either due to the lack of planning or manipulation of the same to favor a minority. To corroborate this statement, the contract ECP-SOC-001-2006 will be analyzed. From the Cartagena ́s refinery modernization project (REFICAR) in which the dimensions of technical and financial requirement to carry it out were certainly not established. An analysis of the investigation will be made by taking as sources some financial audit reports executed by the General Comptroller of the Nation in which the irregularities of this contract can be evidenced.